Expression of a Cystatin Transgene in Eggplant Provides Resistance to Root-knot Nematode, Meloidogyne incognita - Papolu, Pradeep K.; Dutta, Tushar K.; Tyagi, Nidhi; Urwin, Peter E.; Lilley, Catherine J.; Rao, Uma (Frontiers in Plant Science, 2016)
Root-knot nematodes (RKN) cause substantial yield decline in eggplant and sustainable management options to minimize crop damage due to nematodes are still limited. A number of genetic engineering strategies have been developed to disrupt the successful plant-nematode interactions. Among them, delivery of proteinase inhibitors from the plant to perturb nematode development and reproduction is arguably the most effective strategy. In the present study, transgenic eggplant expressing a modified rice cystatin (OC-IΔD86) gene under the control of the root-specific promoter, TUB-1, was generated to evaluate the genetically modified nematode resistance. Five putative transformants were selected through PCR and genomic Southern blot analysis. Expression of the cystatin transgene was confirmed in all the events using western blotting, ELISA and qPCR assay. Upon challenge inoculation, all the transgenic events exhibited a detrimental effect on RKN development and reproduction. The best transgenic line (a single copy event) showed 78.3% inhibition in reproductive success of RKN. Our results suggest that cystatins can play an important role for improving nematode resistance in eggplant and their deployment in gene pyramiding strategies with other proteinase inhibitors could ultimately enhance crop yield.